Deciphering the killing mechanisms of potassium iodide in combination with antimicrobial photodynamic therapy against cross-kingdom biofilm - Li, Yijun; Huang, Shan; Du, Jingyun; Wang, Shaofeng; Cai, Zhiyu; Huang, Xiaojing (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe co-existence of S. mutans and C. albicans is frequently detected in root caries and early child caries and is reported to be associated with recurrent caries. The aim of this study was to investigate the effects of potassium iodide (KI) in combination with toluidine blue O-mediated antimicrobial photodynamic therapy (aPDT) on S. mutans and C. albicans mixed-species biofilm, as well as the antibiofilm mechanisms involved.MethodsMixed-species biofilm was constructed of S. mutans and C. albicans on dentin blocks. The antibiofilm efficacy, cytotoxicity and antibiofilm mechanism of KI in combination with aPDT were determined and evaluated.ResultsKI+TBO-aPDT treatment caused reduction in microorganism counts, metabolic activity, and biofilm biomass of mixed-species biofilm without inducing cytotoxicity to hDPCs (human dental pulp cells). Observations such increased ROS (reactive oxygen species) levels, impaired cell membrane function, cell apoptosis and reduced expression in several genes seem to be artifacts of reduced growth and general killing by KI+TBO-aPDT treatment.DiscussionThese data suggested that KI in combination with aPDT as an innovative approach to combat S. mutans and C. albicans biofilm, and thus as an optional treatment for caries.